Corporate Social Responsibility (CSR) Management and Marketing Communication: Research Streams and Themes - Nielsen, Anne Ellerup; Thomsen, Christa (HERMES - Journal of Language and Communication in Business, 2012)
This article maps the rapidly growing body of research in the field of corporate social responsibility (CSR) management and marketing communication, the focus being on research streams and themes. It evaluates this research from a corporate communication perspective. First, the article examines the concept of CSR communication. A typology of a number of possible domains for CSR communication research is developed, based on the way the different studies conceptualize CSR. Second, the article reviews the concepts of strategic and operative CSR communication which have been adopted widely within the CSR communication literature, relating these to research streams within management and marketing/public relations. Being framed within a corporate communication perspective, the review answers the call for CSR communication research to develop and substantiate outcomes that may better explain or inform CSR communication strategies and practices. A number of categories of outcomes are found within existing empirical studies, and an agenda for building upon this evidence is advanced to allow greater consistency and mutual understanding among CSR communication researchers.